Desenvolvimento de eletrodo modificado com filme de polianilina e estudo da viabilidade da aplicação analítica para catecolaminas - Barbosa, Nathália Vieira (2010)
This work describes the development of a polyaniline (PANI) film modified electrode for determination of dopamine (DA) in pharmaceutical formulation. The electropolymerization of PANI film on platinum electrode was performed by cyclic voltammetry in a solution containing 0.1 mol L-1 aniline monomer and 0.5 mol L-1 sulfuric acid. The study of PANI/Pt electrode electrochemical response for determination of DA was carried out by cyclic voltammetry and differential pulse voltammetry. The DA electrochemical responses was obtained after applying a cathodic pretreatment of the PANI electrode, that consisting in applied a potential of -0.7 V for 3 s before each voltammetric measurements. The DA determination by differential pulse voltammetry, presented a better response in 0.1 mol L-1 phosphate buffer solution at pH 6.5 and using the parameters of scan rate (v), pulse amplitude (a) and pulse increment (ΔEi) of 10 mV s-1, 50 mV and 2 mV, respectively. The calibration curve for dopamine presented linear response in the concentration range between 2.22x10-5 and 3.23x10-4 mol L-1, with detection and quantification limits of 1.80x10-5 and 6.00x10-5 mol L-1, respectively. DA recovery studies fulfilled in pharmaceutical formulation sample using PANI/Pt electrode showed recoveries between 98.0 and 104%. The results obtained with the modified electrode were in agreement with the spectrophotometric method with a relative error of 2.39%. The repeatability of PANI/Pt electrode responses was studied in solution of 1.0 mmol L-1 DA and a relative standard deviation of 2.68% was obtained for ten successive cyclic voltammetry carried out electrode cathodically pretreated before each measurement. The feasibility of analytical application of the proposed electrode for determination of catecholamines was evaluated for the adrenaline, noradrenaline and levodopa. The results obtained showed the applicability of the PANI/Pt electrode. The characterization of the PANI film, performed by field emission gun scanning electron microscopy, showed granular and fibrillar morphology which is a characteristic of PANI.